Community with(out) Others - Willson, Michele (2001)
It is a common claim that the internet provides or enables a liberatory space, a space that is inherently equalising and non-discriminatory. This claim is premised upon two characteristics of internet use. First, the interactive nature of the technology offers all who have access the possibility of being heard - it enables a space for the voice of Others. The second characteristic derives from the fact that most communication online is enacted textually. This method of interaction renders it free from the visual or audile cues of embodied particularities. Thus, those people who experience social or political discrimination on the basis of such particularities are liberated through the act of going online.These claims have some surface truth: it is certainly correct that the technologies of the internet can empower those who have been marginalised, unrepresented or suppressed locally, nationally and globally. However, to adopt these claims uncritically is to fail to recognise the paradoxes inherent in using abstract processes of technology to connect with Others across space and time. This article explores some of these paradoxes, to argue that any claims as to the internet's empowering or disempowering possibilities require critical examination and are less than straightforward or unproblematic.